Egg identification of three economical important fish species using DNA barcoding in comparison to a morphological determination. (27th April 2017) - Hofmann, T.; Knebelsberger, T.; Kloppmann, M.; Ulleweit, J.; Raupach, M. J.
Summary: Accurate identification of fish eggs to species level is a challenging task as many species have similar egg sizes and morphology. The results of egg determination of three economically important fish species are presented by using DNA barcoding in comparison to the classical morphological determination. About 500 fish eggs from the Celtic Sea were collected, morphologically identified and used for DNA analysis. In total, DNA barcodes were successfully obtained from 98% of the investigated eggs, including 167 DNA barcodes from 169 morphologically identified fish eggs of Merluccius merluccius (98.8%), 257 of 262 Scomber scombrus (98.1%), and 47 from 50 Trachurus trachurus (94%). Overall, species identification with DNA barcodes showed a congruence of 96.2% to identification by morphology, whereas 3.8% ( n  =   18) of the analyzed eggs were morphologically assigned to the wrong species. The highest number of incorrect identified eggs was for S. scombrus ( n  =   15). Our study highlights the usefulness of DNA barcoding for valid fish egg identification but also indicates the robustness of the classical morphology‐based approach.